2008
DOI: 10.1108/01445150810863699
|View full text |Cite
|
Sign up to set email alerts
|

Proper constraint as a design principle for assemblies

Abstract: PurposeThis paper's objective is to explain the concept of proper kinematic constraint to guide requirements‐driven design of mechanical assemblies and to connects proper constraint to the datum flow chain (DFC) and key characteristics (KCs).Design/methodology/approachThe paper presents proper constraint as a way to support the goal of placing key parts in particular geometric relationships with respect to one another so that a DFC can deliver KCs unambiguously. Such a DFC is said to be competent. Additionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Some research on the factors that influenced the performance of ecotourism and the level of tourist arrivals to the ecotourism area, such as Bezzina and Grima (2012); Binion and Chen (2017), Shimotani et al (2016); Suhr and Rubeša (2013); Whitney (2008); Behm et al (2000); Cheng et al (2002); Njoroge et al (2017); Tucker and Lean (2003); Zhang et al (2002). Those research studies examined the effect of Quality of Local Population on the Performance of Ecotourism.…”
Section: Introductionmentioning
confidence: 99%
“…Some research on the factors that influenced the performance of ecotourism and the level of tourist arrivals to the ecotourism area, such as Bezzina and Grima (2012); Binion and Chen (2017), Shimotani et al (2016); Suhr and Rubeša (2013); Whitney (2008); Behm et al (2000); Cheng et al (2002); Njoroge et al (2017); Tucker and Lean (2003); Zhang et al (2002). Those research studies examined the effect of Quality of Local Population on the Performance of Ecotourism.…”
Section: Introductionmentioning
confidence: 99%
“…Long and Hu (1998) extend the analysis model by incorporating position variations of fixture locators into the model. Whitney (2008) presents proper constraints as a way to support the goal of placing key parts in particular geometric relationship with respect to one another so that a DFC can deliver KCs unambiguously. Merkley (1998) recognizes the need to include covariance in statistical FEAs when random variables are used for input.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial studies of the tolerance analysis and synthesis have been conducted (Singh et al, 2005;Shen et al, 2008;Shao et al, 2008). Whitney (2008) found that some designs required tight tolerances on the over-constrained degrees of freedom and most tolerance analysis software did not test designs for their state of constraint and might yield incorrect answers. The tolerance stack-up methods can be categorized into three types that are the worst-case method, the root-sum-square (RSS) method, and the statistical modeling method.…”
Section: Introductionmentioning
confidence: 99%